REKONDISI SISTEM VERTICAL MOVEMENT PADA MESIN PRECISION UNIVERSAL AND TOOL & CUTTER GRINDER TYPE JUNGNER US-350 - Zika Lorika; Boy Rollastin; Sukanto Sukanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
This study aims to recondition the vertical movement system of the Precision Universal and Tool & Cutter Grinder Jungner US-350 to restore the optimal functionality of the vertical head. The machine experienced failures in the threaded bushing, timing belt, and flat belt, affecting the cutting tool grinding process. The research applied an experimental approach, including data collection through technician interviews, visual inspection, and machine manual review, fault identification using the 5 Whys method, and repair or replacement of critical components according to technical specifications. Functional testing demonstrated smooth vertical movement, stable timing and flat belt operation, and machine performance meeting precision standards. The study shows that structured reconditioning is an effective solution for restoring the functionality of aging precision machines with limited spare parts, while providing practical guidance for maintenance and care of similar machines.